Panoramic radiography, conventional and reformatted 3D computed tomography in diagnosis of mandibular fractures - Omniya Mahmoud Hussien Abueldahab; Hany Mahmoud Omar; Mohamed Baher Tewfik; Mushira Mohamed Dahaba (Cairo : Omniya Mahmoud Hussien Abueldahab, 2008)
This study was performed to assess the validity and exact role of conventional and multiplannar reconstructed (MPR) 3DCT as well as panormic radiography in diagnosis of mandibular fractures. Eight adult patients with varying traumatic injuries that resulted in fourteen mandibular fractures were included in this study
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral Radiology and Diagnosis
Issued also as CD
Keywords: CT; Mandibular fractures; Panoramic radiography